Are we overdosing treatment? Secondary findings from a study following women with bulimia nervosa after inpatient treatment. Issue 8 (2nd August 2018) - Beintner, Ina; Jacobi, Corinna
Abstract: Objective: Provision of eating disorder (ED) treatment in practice is often guided by national health service structures rather than evidence‐based treatment recommendations. Especially for more severely or chronically ill patients, clinicians seem to advocate a "the more the better" strategy of treatment provision. Exploring the dose‐response relationship in ED treatment may shed light on both beneficial and detrimental effects of prolonged treatment provision. Method: We utilized data from 64 women from the treatment‐as‐usual (TAU) group of a randomized controlled trial on Internet‐based aftercare for women with bulimia nervosa who had received inpatient treatment. We examined the relationship between treatment duration and dose and (1) baseline patient characteristics and (2) treatment outcomes (abstinence from binge eating and compensatory behaviors, frequency of binge eating and vomiting, thin ideal internalization, and general psychopathology) at 18‐month follow up. Results: On average, the women in our study were hospitalized for 9 weeks and most received high doses of subsequent outpatient psychotherapy (median: 45 sessions). The severity of symptoms that a patient experienced at hospital admission or discharge was largely unrelated to the amount of outpatient treatment she subsequently received. Longer inpatient treatments or higher doses of subsequent outpatient treatment did not result in more favorable outcomes. Discussion: Our findings suggest that, instead of providing costly long treatment without evidenced benefit to patients, there is a need for further exploration of and discussion about the risks and benefits of providing high doses of treatment for both individuals and the health care system.